The Doctrine of Siyasah in the Hanafi Criminal Law and Its Relevance for the Pakistani Legal System - Ahmad, Muhammad Mushtaq (Islamic Studies, 2013)
The paper argues that a clear understanding of the doctrine of siyasah in the Hanafi criminal law, an ignored area in the deleberations on Islamic criminal law in the post-colonial world, is of vital importance in resolving the conflicts and contradictions existing in the Pakistani laws. The basic contention of the paper is that the classification of rights violated by a crime forms the backbone of the Hanafi criminal law the ignorance of which causes basic confusions. The paper shows that the usage of term ta‘zir in Hanafi law covers a broad range of punishments: punishments laid down by the ruler for offences generally, lesser punishment in cases of hudud and qisas offences and private disciplinary actions. The last of these categories relates to the right of individual and as such it should be excluded from the domain of criminal law. The remaining categories, siyasah and ta‘zir, relate to the right of the ruler and they have almost similar consequences, except for the standard of proof and the limit of punishment. The paper concludes that the doctrine of siyasah can offer better solutions for the complicated problems of the Pakistani criminal justice system, such as blasphemy, rape and pardon in murder cases as well as admissibility of the testimony of women.